Sam Shepard's plays according to Slovenian theatre directors - Anina Oblak (Acta Neophilologica)
The article focuses on the productions of Sam Shepard's plays in Slovenia during 1985-2000 and the author of the paper primarily pays attention to the Slovenian directors' approach to Shepard's works and the problems that have arisen in the process. Five of Shepard's plays have been staged to date in Slovenia, two early works and three works of new realism. In interviews with the directors (Vinko Möderndorfer, Primož Bebler, Boris Kobal, Dušan Jovanovic and Boris Cavazza) as well as three actresses and a choreographer (Alenka Vidrih, Barbara Babič, Vesna Jevnikar, Tanja Zgonc) it has emerged that the transplantation of typically American issues to Slovenia and their treatment necessitated a different approach from the one normally taken by the Slovenian directors and actors. Shepard's plays being idiosyncratic, the theatre artists had to either accommodate his material or treat it with different methods that were adapted to suit the Slovenian environment.